META-ANALYfICAL REVISION OF THE RELATIONSHIP BE1WEEN CARlSMATlC LEADRSHlP AND ORGANIZATIONAL PERFOMANCE - Borrero Caldas, Silvio; Ossa Flórez, Gustavo Andrés; Tascón Durán, Gustavo Adolfo (Cuadernos de Administración, 2008)
Despite the importance that the specialized literature gives to the leadership in organizations, There isn't a model that adequately explains the processes through which Leaders influence their followers nor the degree oftransfonnation resulting in the organization. Researches over the past two decades suggest a positive relationship between the leader 's charisma and organizational performance, and the presence of factors that moderate the intensity of this relationship. We suggest that there is a not mediated relationship between charismatic leadership and organizational perfonnance, that this relationship is maintained when the analysis is restricted to financial indicators, that the relationship is moderated by environmental uncertainty, and that the size ofthe organization exerts a negative moderating effect on the relationship. It consolidated a set of 22 magnitudes effect which was successively refmed to test different hypothesis through a metaanalysis using the VG2M sirnulator. This paper discusses the results of the simulation and develops conclusions from the same.